PEMBERDAYAAN MASYARAKAT PETANI GARAM MELALUI HOME INDUSTRY GARAM BERYODIUM DI DESA SANOLO - agrippina wiraningtyas; ruslan r; sry agustina (Program Studi Pendidikan Kimia STKIP Bima, 2018)
Community empowerment program has been carried for salt farmers in the Sanolo village through iodized salt home industry. The goal of this programe to improve the quality of the salt harvest salt farmers in the Sanolo village Bima regency through the creation of iodized salt. To standarized food needs by improving the quality of local salt accordance with the Indonesian National Standard (SNI). Promoting and marketing of iodized salt. Establish a local institution in the salt farming community. The method used in this activity is done through several steps including socialization, training iodized salt production, management training and marketing and publication of products. This programe was produced several conclusions including the salt harvest of farmers in the village of Sanolo can improve the quality and resale value through the production of iodized salt. Iodized salt produced by home industry in the Sanolo village meet the Indonesian National Standard (SNI) as the salt consumption. Community organizations have formed for the management of iodized salt by organization is